DESIGN, IMPLEMENTATION, AND EVALUATION OF PAI LEARNING (Research Study at Nurul Islam Karawang Integrated Quran Elementary School) - Iqbal Amar Muzaki; Sofia Ratna Awaliyah Fitri; Aji Saepurahman; Uus Ruswandi (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Evaluation or assessment is an integral part of the learning process. Evaluation is a component in the learning process carried out by applying several principles, namely continuity, comprehensive, cooperative, objective and practical. Islamic Religious Education at the Integrated Quran Dasat School (SDQT) Nurul Islam consists of combining government curriculum subjects and Foundation and extracurricular curricula. This study used two research methods. Field Research and Library Research. Therefore, this research is included in the qualitative research category. The results showed that the learning evaluation design process at the Nurul Islam Integrated Quran Elementary School (SDQT) refers to the principle of learning by applying formative and summative assessment patterns.